2022
DOI: 10.31822/2022-7-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Medical Tourism in the Turkish Republic of Northern Cyprus: Strategies for Improvement

Abstract: Right to health" is a fundamental human right and it is protected by international laws, also it turns over to states in three areas. Quality health care, affordability and the availability of necessary facilities and equipment's form part of the reasons why individuals in need of these services migrate to countries that fortunately have upgraded facilities ready to serve the needs of patients worldwide. The purpose of this study is to examine the perceptions of health practitioners, tourist agents (travel age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They suggested that health tourism providers should utilize social media platforms to engage with tourists, provide valuable information, and create personalized experiences to attract more visitors. In the context of TRNC, a study by Arueyingho, Ghasemi & Bodamyalı (2022) investigated the perceptions of medical tourists about the quality of healthcare services in the country. The study found that medical tourists were generally satisfied with the medical services provided in TRNC, particularly in terms of cost-effectiveness and the quality of medical staff.…”
Section: The Development and Success Of Health Tourismmentioning
confidence: 99%
“…They suggested that health tourism providers should utilize social media platforms to engage with tourists, provide valuable information, and create personalized experiences to attract more visitors. In the context of TRNC, a study by Arueyingho, Ghasemi & Bodamyalı (2022) investigated the perceptions of medical tourists about the quality of healthcare services in the country. The study found that medical tourists were generally satisfied with the medical services provided in TRNC, particularly in terms of cost-effectiveness and the quality of medical staff.…”
Section: The Development and Success Of Health Tourismmentioning
confidence: 99%